The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1600-051x.2005.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on the clinical, microbiological and immunological parameters of adult patients with periodontitis

Abstract: Current data indicate that smokers with periodontal disease have a suppressed inflammatory response, a significantly less favourable clinical outcome and seem to have an altered host antibody response to antigenic challenge than non-smokers. In contrast, the subgingival microflora of smokers appears similar to that of non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
165
4
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(201 citation statements)
references
References 63 publications
21
165
4
11
Order By: Relevance
“…A three way interaction involving smoking treatment and the visit was shown previously to influence clinical measurements at selected sites [20] at R1 but not at R2 when the clinical improvements and healing time were seen to be similar [19,20]. Although we saw no difference in baseline values between smokers and nonsmokers, smoking appears to have influenced the results observed post-treatment.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…A three way interaction involving smoking treatment and the visit was shown previously to influence clinical measurements at selected sites [20] at R1 but not at R2 when the clinical improvements and healing time were seen to be similar [19,20]. Although we saw no difference in baseline values between smokers and nonsmokers, smoking appears to have influenced the results observed post-treatment.…”
Section: Discussioncontrasting
confidence: 44%
“…Full-mouth periodontal assessments were carried out by the same examiner (DAA) at baseline, 6-weeks (R1) after treatment and six months (R2) from baseline assessment [19,20]. For the FM-SRP group R1 was on week 7 and for the Q-SRP group on week 13.…”
Section: Clinical Examination and Sample Collectionmentioning
confidence: 99%
“…2 It remains unclear whether there are differences in the subgingival biofilm composition between SM and NS. Some studies have shown no differences in the prevalence of periodontal pathogens 13,14,15 while other studies have demonstrated higher levels of periodontal pathogens belonging to the red and orange complexes 10,11,12 in SM compared to NS. The present study assessed the prevalence of A. actinomycetemcomitans, P. gingivalis, and T. forsythia at baseline and at 3 and 6 months of treatment and found that only A. actinomycetemcomitans was statistically higher at baseline in SM compared to NS.…”
Section: Discussionmentioning
confidence: 99%
“…13,35 In the current study, the reduction in the levels of periodontopathogens (A. actinomycetemcomitans, P. gingivalis, and T. forsythia) in both groups (SM and NS) was 100% after 6 months of therapy. A significant reduction of T. forsythia and A. actinomycetemcomitans levels in both SM and NS, absence of P. gingivalis among NS, and very low detection of P. gingivalis among SM (less than 10%) were observed after 6 months of periodontal treatment in a study conducted by Aptzidou et al 14 The same magnitude of microbiological response was observed for P. gingivalis and T. forsythia 6 months after periodontal treatment in SM and NS by Renvert et al 35 However, these authors observed that A. actinomycetemcomitans increased in SM, demonstrating that this pathogen is more difficult to be eradicated among tobacco users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation